PENGARUH PEMBUKUAN DIGITAL TERHADAP PENGELOLAAN ARUS KAS PADA UMKM DI KECAMATAN RAPPOCINI KOTA MAKASSAR - Ayuningsih, Retno; Aisyah, Siti; Alamsjah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine whether the use of digital bookkeeping has an effect on cash flow management in Micro, Small, and Medium Enterprises (MSMEs) in Rappocini District, Makassar City. The background of this study is based on the fact that many MSME owners, particularly in the culinary sector, still use manual financial recording methods. This approach is considered inefficient as it is prone to errors and requires more time to produce financial reports. Digital bookkeeping presents a solution that enables MSMEs to record transactions automatically, generate more accurate and timely financial reports, and monitor cash flow in real-time. This study employed an associative quantitative approach. The variables studied were digital bookkeeping as the independent variable (X) and cash flow management as the dependent variable (Y). Data were collected through questionnaires distributed to 164 culinary MSME owners in Rappocini District as the research sample, selected from a total population of 278 MSMEs using the Slovin formula with a five percent margin of error. Data were analyzed using simple linear regression. The results indicate that digital bookkeeping has a positive and significant effect on cash flow management of MSMEs in Rappocini District, Makassar City, with t-count 8.381 > t-table 1.975 and significance value 0.000 < 0.05. The coefficient of determination (R²) shows that digital bookkeeping explains 30.2% of the variation in cash flow management.